1999
DOI: 10.1289/ehp.99107843
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to polychlorinated biphenyls and levels of thyroid hormones in children.

Abstract: As part of an epidemiologic study on exposure to a toxic waste incineration plant we investigated whether blood concentrations ofpolychlorinated biphenyls (PCBs), lead, and cadmium, as well as concentration of mercury in 24-hr urine samples were associated with thyroid hormone status. As an indication of stats, we detennined levels of thyroid-stimulating hormone (TSH), free thyroxine (FT4), and free triiodothyronine (FT3) in children living in households where < 10 cigarettes were smoked per day. Eight PCB con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
3
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(91 citation statements)
references
References 27 publications
6
81
3
1
Order By: Relevance
“…Consistent with our results was a recent Canadian study of 149 pregnant women found a significant inverse relationship between low, environmental levels of HCB, PCB 153 and ΣPCBs in plasma and total T 3 , but no associations with free T 4 and TSH (Takser et al 2005). Likewise, inverse associations between PCBs and T 3 levels were also previously observed in the wives of Swedish fishermen (Hagmar et al 2001b) and in German schoolchildren (Osius et al 1999), while another study among Dutch women reported an inverse association with T 3 that was also accompanied by an inverse association with T 4 and a positive association with TSH (Sala et al 2001). Other studies have reported an inverse association between PCBs, and T 4 and/or a positive association between PCBs and TSH, with no association between PCBs and total T 3 (Schell et al 2004;Hagmar 2003;Persky et al 2001;Emmett et al 1988), while another reported no associations between PCBs and thyroid hormones among 160 neonates from North Carolina from 1978 to 1982 (Longnecker et al 2000).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our results was a recent Canadian study of 149 pregnant women found a significant inverse relationship between low, environmental levels of HCB, PCB 153 and ΣPCBs in plasma and total T 3 , but no associations with free T 4 and TSH (Takser et al 2005). Likewise, inverse associations between PCBs and T 3 levels were also previously observed in the wives of Swedish fishermen (Hagmar et al 2001b) and in German schoolchildren (Osius et al 1999), while another study among Dutch women reported an inverse association with T 3 that was also accompanied by an inverse association with T 4 and a positive association with TSH (Sala et al 2001). Other studies have reported an inverse association between PCBs, and T 4 and/or a positive association between PCBs and TSH, with no association between PCBs and total T 3 (Schell et al 2004;Hagmar 2003;Persky et al 2001;Emmett et al 1988), while another reported no associations between PCBs and thyroid hormones among 160 neonates from North Carolina from 1978 to 1982 (Longnecker et al 2000).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, several human studies have investigated associations between levels of these compounds in the body and thyroid hormone levels (Takser et al 2005;Schell et al 2004;Bloom et al 2003;Hagmar 2003;Pelletier et al 2002;Hagmar et al 2001a;2001b;Persky et al 2001;Sala et al 2000;Longnecker et al 2000;Osius et al 1999;Koopman-Esseboom et al 1994;Emmett et al 1988). However, study populations have differed greatly and results have not been consistent across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Increase in TSH level or decrease in T3 (free or total) or total T4 have been observed in most studies (Alvarez-Pedrerol et al 2008b;Darnerud et al 2010;Herbstman et al 2008;Koopman et al 1994;Osius et al 1999), except in Matsuura et al (2001) and Dallaire et al (2009).…”
Section: Introductionmentioning
confidence: 82%
“…No consistent associations with a specific thyroid hormone have been observed, although positive results of some sort have been found in several studies (Hagmar et al 2001;Koopman-Esseboom et al 1994;Osius et al 1999;Persky et al 2001). In animal experiments, PCBs decrease serum levels of thyroxine (Brouwer et al 1999).…”
Section: Endocrine Disruption As a Hypothesis In Human Studiesmentioning
confidence: 98%